Pelatihan Pengolahan Jagung bagi Masyarakat Dusun Senyiur Kabupaten Lombok Timur - Safnowandi, Safnowandi; Abidin, Zainal; Dewi, Ika Nurani; Efendi, Ismail; Utami, Septiana Dwi (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2022)
Senyiur Hamlet is one of the hamlets located in Senyiur Village, Keruak District, East Lombok Regency. The purpose of this service activity is to increase the knowledge and skills of the community in Senyiur Hamlet about processing corn into Corn Cake. In addition, it can provide alternative post-harvest handling of corn, especially corn that is able to produce products that are acceptable to consumers, provide alternatives to consumers of corn-based products, and open up opportunities for developing agribusiness-based home industries. Methods of activities carried out include: 1) Site surveys and discussions on the technical implementation of activities with partners (Head of Senyiur Hamlet); 2) Determination of targets to be invited, resource persons who will provide knowledge and training; 3) Determination of students who will become assistants when making processed corn products; 4) Submission of materials on the benefits and various processed products based on Corn; 5) Demonstration of processing corn pudding, corn cake and ice corn and 6) Evaluation of Target Knowledge and Motivation. Based on this activity, it is hoped that there will be an increase in community knowledge and skills in processing corn into snacks that have high economic value.